Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Frederik Thiele; Thomas Hummel; Nina Amelie Lange; Felix Dreher; Maximilian Protte; Felix vom Bruch; Sebastian Lengeling; Harald Herrmann; Christof Eigner; Christine Silberhorn; Tim J Bartley (Materials for Quantum Technology, 2024)
Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO _3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.